Role of Mitochondria in Cancer Immune Evasion and Potential Therapeutic Approaches - Klein, Katherine; He, Kewen; Younes, Ahmed I.; Barsoumian, Hampartsoum B.; Chen, Dawei; Ozgen, Tugce; Mosaffa, Sara; Patel, Roshal R.; Gu, Meidi; Novaes, Jose; Narayanan, Aarthi; Cortez, Maria Angelica; et al. (Frontiers in Immunology, 2020)
The role of mitochondria in cancer formation and progression has been studied extensively, but much remains to be understood about this complex relationship. Mitochondria regulate many processes that are known to be altered in cancer cells, from metabolism to oxidative stress to apoptosis. Here we review the evolving understanding of the role of mitochondria in cancer cells, and highlight key evidence supporting the role of mitochondria in cancer immune evasion and the effects of mitochondria-targeted antitumor therapy. Also considered is how knowledge of the role of mitochondria in cancer can be used to design and improve cancer therapies, particularly immunotherapy and radiation therapy. We further offer critical insights into the mechanisms by which mitochondria influence tumor immune responses, not only in cancer cells but also in immune cells. Given the central role of mitochondria in the complex interactions between cancer and the immune system, high priority should be placed on developing rational strategies to address mitochondria as potential targets in future preclinical and clinical studies. We believe that targeting mitochondria may provide additional opportunities in the development of novel antitumor therapeutics.